Fault Management in Network Virtualization Environment - Ying Wang; Lu Guan (Dianxin kexue)
Network virtualization is one of the important features and evolving directions of future network.It is very important for the robustness,survivability and manageability of the network virtualization environment（NVE）to localize fault timely and accurately as well as recover from fault quickly.However,traditional fault management mechanisms could not deal with such features of NVE as enlarged scale,multi-layer and uncertainty of mapping relationships.It is necessary to research fault management mechanisms for NVE.The fault management process in NVE was presented,and a survey of some recent work on this topic was offered.